Illvstriss.mo Principi Ac Domino, Dn. Gvlielmo, Saxon. Ivl. Cliv. Mont. Dvci, Landgr. Tvring. Marchio Misnensivm Com. March. Et Ravensp. Dn. In Ravenst. etc - Richter, Christian (1662)
Bildoval, Bruststück, in Rüstung